Endovascular recanalization for chronic symptomatic middle cerebral artery total occlusion. (11th April 2012) - Ma, Ning; Mo, Da-Peng; Gao, Feng; Miao, Zhong-Rong
Abstract : The optimal treatment of chronic middle cerebral artery (MCA) occlusion is unclear. Angioplasty and stenting may be an alternative treatment for patients with recurrent ischemic symptoms despite medical therapy. Two patients with chronic right MCA occlusion successfully treated with stenting are reported, together with their long term follow-up to illustrate the feasibility of endovascular recanalization. One patient remained asymptomatic at the 29-month follow-up. Another patient developed symptomatic in-stent restenosis at 12 months which resolved after repeat angioplasty. Further larger scale pilot studies are needed to determine the efficacy and long term outcome of this treatment.